Illicit Sex and the Female Researcher: Reflections from the Field - Parker, Katharine (feminists@law, 2016)
This article presents some initial methodological reflections from an ongoing programme of empirical research examining the risk taking behaviours of men who have sex with men in public sex environments in an urban area of North East England. Drawing upon an early career female researcher’s experience of undertaking sixteen in-depth interviews with male participants, this paper seeks to critically explore the challenges that female researchers face when conducting interviews with men on topics related to sexuality and sexual risk behaviours.